2021
DOI: 10.1002/jcsm.12690
|View full text |Cite
|
Sign up to set email alerts
|

The value of spot urinary creatinine as a marker of muscle wasting in patients with new‐onset or worsening heart failure

Abstract: Background Muscle wasting and unintentional weight loss (cachexia) have been associated with worse outcomes in heart failure (HF), but timely identification of these adverse phenomena is difficult. Spot urinary creatinine may be an easily accessible marker to assess muscle loss and cachexia. This study investigated the association of urinary creatinine with body composition changes and outcomes in patients with new‐onset or worsening HF (WHF). Methods In BIOSTAT‐CHF, baseline spot urinary creatinine measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Previous research suggested that in multivariate models, SUCR values were positively correlated with kidney function and hemoglobin in GISSI-HF [14], diastolic blood pressure, and serum sodium in BIOSTAT-CHF [15]. The negative correlation of SUCR was identified with urinary albumin, diabetes, age, diuretic use, NYHA class, sex, and fibrinogen levels in GISSI-HF [14] and with serum urea nitrogen, peripheral oedema above the ankles, presence of orthopnea, plasma NTproBNP, and female sex in BIOSTAT-CHF [15]. None of these determinants were independent risk factors for low SUCR in our analysis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous research suggested that in multivariate models, SUCR values were positively correlated with kidney function and hemoglobin in GISSI-HF [14], diastolic blood pressure, and serum sodium in BIOSTAT-CHF [15]. The negative correlation of SUCR was identified with urinary albumin, diabetes, age, diuretic use, NYHA class, sex, and fibrinogen levels in GISSI-HF [14] and with serum urea nitrogen, peripheral oedema above the ankles, presence of orthopnea, plasma NTproBNP, and female sex in BIOSTAT-CHF [15]. None of these determinants were independent risk factors for low SUCR in our analysis.…”
Section: Discussionmentioning
confidence: 91%
“…Replacement of timely urine collection with spot urinary creatinine (SUCR) concentration would overcome at least part of these limitations. Two recent studies have shown the association of low SUCR with muscle wasting and with poor prognosis in HF patients [14,15]. However, the risk factors for SUCR that clearly increase mortality risk are not identified yet.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of serum creatinine, produced after stable conversion of creatine largely found in skeletal muscles, can also be used as a marker to reflect (peripheral) muscle catabolism and is an established marker of muscle mass 28 , and can be used as a measure of cachexia 29, 30 . The adjusted formula and use of spot urine samples was validated in a heart failure population using data from the Additive renin Inhibition with Aliskiren on renal blood flow and Neurohormonal Activation in patients with Chronic Heart Failure and Renal Dysfunction cohort (ARIANA-CHF-RD) 31 . GDF15 inversely correlated with urinary creatinine (Figure 6b).…”
Section: Resultsmentioning
confidence: 99%
“…Using a cohort of patients with heart failure, we showed that GDF15 measured in plasma correlated with surrogate markers in urine for protein intake and muscle mass. Although the study utilised spot urine samples rather than a 24 hr urine sample, our recent study using spot urine analysis showed that urinary creatinine concentrations were associated with smaller body dimensions (lower BMI, height, and weight) and an increased risk of ( > 5%) weight loss at 9 months 31 . The inverse correlation of muscle mass and protein intake with GDF15 and raised GDF15 levels in patients with cachexia, support the concept that GDF15 plays a role in driving cardiac cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…An inverse relationship between the creatinine level and MS has been recently reported and serum levels of CRP and creatinine have been proposed as potential biomarkers for neurodegenerative diseases [ 52 ]. Creatinine is a biomarker directly related to muscle mass [ 53 ]. Therefore, we suggest that a reduction in inflammation and fatigue observed after treatment with the multivitamin supplement could have facilitated greater muscle activity in MS patients, and that the latter, in turn, could have reduced inflammation, thus triggering a beneficial self-sustaining mechanism leading to a further reduction in inflammation, possibly due to the greater availability of patients to movement.…”
Section: Discussionmentioning
confidence: 99%